Thymidylate synthase expression as a predictive biomarker of pemetrexed sensitivity in advanced non-small cell lung cancer. Issue 1 (December 2015) - Chamizo, Cristina; Zazo, Sandra; Dómine, Manuel; Cristóbal, Ion; García-Foncillas, Jesús; Rojo, Federico; Madoz-Gúrpide, Juan
Abstract Background Although it has been suggested that a high level of thymidylate synthase (TYMS ) gene expression in malignant tumors is related to reduced sensitivity to the antifolate drug pemetrexed, no direct evidence for such an association has been demonstrated in routine clinical samples from patients treated with the drug. The purpose of this study was to quantitatively assess the impact ofTYMS gene expression in tumor cells as a predictor of the efficacy of pemetrexed therapy in patients with advanced non-small cell lung cancer (NSCLC) treated at our institution. Methods Sixty-two NSCLC patients were included in this study: 16 patients received platins-pemetrexed as first-line NSCLC, and 46 pemetrexed in monotherapy as second- or subsequent-line treatment. Total mRNA was isolated and the expression ofTYMS was analyzed by RT-qPCR.TYMS levels were calibrated against expression in normal lung tissue. Results TYMS overexpression was detected in 61 % of patients and low expression in 39 %. The response rate for patients with lowTYMS expression was 0.29 compared with 0.03 in patients with overexpression (P =  0.025). A significant benefit was observed in patients with low expression both in time to progression (average TTP = 56 vs. 23 months, P =  0.001) and in overall survival (average OS = 60 vs. 25 months, P =  0.002). Conclusions TYMS overexpression in tumor cells correlated with a reduced response to pemetrexed-containing chemotherapy and might be used as a predictive biomarker in advanced NSCLC patients.